Korelasi Kemampuan Profesional Dengan Prestasi Kerja Jabatan Fungsional Umum (Jfu) Di Lingkungan Kementrian Agama Kota Padang - Eldison Eldison (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2020)
This study aims to find out in real terms about the existence of a positive or significant influence between Professionalism possessed General Functional Position (JFU). The method used is survey method by applying Grounded Research. The population in this study is all JFU in the environment of the Ministry of Religious Affairs of Padang City with the number of 200 JFUs comprising JFU in Madarasah Aliyah in Padang City, Madrasah Tsanawiyah, Madrasah Ibtidaiyah and Office of Religious Affairs of Padang City. Sample in this research is counted 50 people with random sampling technique. Data Collection Technique uses questionnaire. The variables measured are independent variables, namely: Professionalism (X), while the dependent variable is Work Achievement (Y). The results of this study show that professionals affect job performance of General Functional Position (JFU). This is seen in the value of tcount> ttable (2.53 > 2). Furthermore, professionalism also affects the effectiveness of ASN work with tcount> ttable (3.79 > 2,002). By parsila influence of JFU professionalism to performance achievement of JFU with result of analysis that is Fcount > Ftsbel (14,15 > 3,15). Based on these analysts can be concluded that professionalism in parsila mempenguruhi performance JFU work at the Office of the Ministry of Religious City of Padang.